2021
DOI: 10.1002/pmrj.12662
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of function‐limiting late effects in Hodgkin lymphoma survivors

Abstract: Background: Hodgkin lymphoma (HL) is highly curable, but survivors often develop function-limiting impairments. Screening guidelines for neuromuscular and musculoskeletal late effects are not as well recognized across medical disciplines. Early identification and management of functional late effects are instrumental in improving the longitudinal care of HL survivors. Objective: To define the prevalence of neuromuscular, musculoskeletal, visceral, oncologic, and other late effects affecting function and qualit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…MRI con rmed signs of cervical muscle atrophy in 80% of these cases, whereas muscle atrophy could not be detected in CCS without clinical or neurological signs of DHS who received MRI as part of their routine cancer follow-up. Few former studies indicated a much higher prevalence of radiation-induced DHS in HL survivors up to 83% in a recent analysis in which, however, diagnosis of DHS was solely based on subjective weakness in head elevation or weak cervical paraspinal muscle contraction demonstrated during palpation on physical exam [30]. Furthermore, only survivors visiting a cancer rehabilitation outpatient clinic for functional impairments have been included [30] so that, similar to another study on progressive muscle atrophy in HL survivors in which a relevant share of potential survivors could not be included in the study due to multiple reasons [8], data did not allow to draw conclusions on the true incidence of radiation-induced DHS in an unselected cohort of CCS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MRI con rmed signs of cervical muscle atrophy in 80% of these cases, whereas muscle atrophy could not be detected in CCS without clinical or neurological signs of DHS who received MRI as part of their routine cancer follow-up. Few former studies indicated a much higher prevalence of radiation-induced DHS in HL survivors up to 83% in a recent analysis in which, however, diagnosis of DHS was solely based on subjective weakness in head elevation or weak cervical paraspinal muscle contraction demonstrated during palpation on physical exam [30]. Furthermore, only survivors visiting a cancer rehabilitation outpatient clinic for functional impairments have been included [30] so that, similar to another study on progressive muscle atrophy in HL survivors in which a relevant share of potential survivors could not be included in the study due to multiple reasons [8], data did not allow to draw conclusions on the true incidence of radiation-induced DHS in an unselected cohort of CCS.…”
Section: Discussionmentioning
confidence: 96%
“…Few former studies indicated a much higher prevalence of radiation-induced DHS in HL survivors up to 83% in a recent analysis in which, however, diagnosis of DHS was solely based on subjective weakness in head elevation or weak cervical paraspinal muscle contraction demonstrated during palpation on physical exam [30]. Furthermore, only survivors visiting a cancer rehabilitation outpatient clinic for functional impairments have been included [30] so that, similar to another study on progressive muscle atrophy in HL survivors in which a relevant share of potential survivors could not be included in the study due to multiple reasons [8], data did not allow to draw conclusions on the true incidence of radiation-induced DHS in an unselected cohort of CCS. Our proposed algorithm for radiation-induced DHS diagnosis showed good reliability and practicability in a clinical setting without risks of radiation exposure or invasive procedure.…”
Section: Discussionmentioning
confidence: 96%
“…No group of cancer survivors better exemplifies our need to embrace complexity more than those afflicted with radiation late effects—particularly those treated for Hodgkin lymphoma (HL) and head and neck cancer (HNC). A recent retrospective cohort analysis of 100 consecutive HL survivors evaluated and treated in the outpatient cancer rehabilitation setting demonstrates that nearly all had neuromuscular dysfunction including subacute myelopathy (83%), radiculo-plexopathy (93%), mononeuropathy (95%), and localized myopathy (93%) or a combination of all termed “myelo-radiculo-plexo-neuro-myopathy” [ 3 •]. Dropped head syndrome (83%), cervicalgia (79%) and shoulder girdle dysfunction (73%), and pain (71%) were some of the most common disorders seen.…”
Section: Clinical Complexitymentioning
confidence: 99%
“…A more medically focused review listed loss of saliva, osteoradionecrosis, radiation recall myositis, pharyngoesophageal stenosis, dental caries, oral cavity necrosis, fibrosis, impaired wound healing, skin changes and skin cancer, lymphedema, hypothyroidism, hyperparathyroidism, lightheadedness, dizziness and headaches, secondary cancer, and eye, ear, neurological, and neck structure damage as late effects [ 5 ]. Baroreflex failure is considered rare but likely underrecognized and diagnosed in HNC and HL survivors [ 3 •, 6 ]. Radiotherapy-induced carotid toxicity is common in HNC and likely other groups such as HL survivors [ 3 •, 7 ].…”
Section: Clinical Complexitymentioning
confidence: 99%
See 1 more Smart Citation